2012
DOI: 10.1590/s0102-311x2012000400003
|View full text |Cite
|
Sign up to set email alerts
|

Atendimentos decorrentes de queimaduras em serviços públicos de emergência no Brasil, 2009

Abstract: O objetivo foi analisar os atendimentos por queimaduras em serviços de emergência, e fatores associados. Estudo transversal de 761 atendimentos coletados pelo Sistema de Vigilância de Violências e Acidentes em 2009. A maioria foi do sexo masculino (58,6%); adultos de 30 a 49 anos (23,1%) e crianças de 0 a 9 anos (23%). A residência foi o local de ocorrência mais frequente (62,1%), especialmente para crianças e mulheres; em seguida comércio, serviços, indústria e construção (19,1%), especialmente entre homens d… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
19
0
28

Year Published

2015
2015
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(48 citation statements)
references
References 8 publications
1
19
0
28
Order By: Relevance
“…9 A study among employees of power distribution companies in Iran showed that individuals of working age, who are married, and who have a high education and temporary work contracts, were the most affected by occupational electric injuries. 14 According to the testimony, the visibility of burning risk situations when handling the work equipment generates fear and apprehension, becoming an intrapersonal stressor, so that the subjects need to pay constant attention when handling the equipment due to the possibility of accidents.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…9 A study among employees of power distribution companies in Iran showed that individuals of working age, who are married, and who have a high education and temporary work contracts, were the most affected by occupational electric injuries. 14 According to the testimony, the visibility of burning risk situations when handling the work equipment generates fear and apprehension, becoming an intrapersonal stressor, so that the subjects need to pay constant attention when handling the equipment due to the possibility of accidents.…”
Section: Discussionmentioning
confidence: 99%
“…[8][9][10] Studies focused on knowledge of the circumstances surrounding work-related burn injuries from the workers' perspective may contribute to identification of the main risks/ stressors for these accidents 9 and the detection of appropriate prevention measures to reduce these injuries, which is the relevance of the present research. 10 In order to analyze the perception of workers who suffer burn injuries regarding environmental risk, the Neuman Systems Model, 2 proposed by Betty Neuman in 1970, was used as a theoretical framework.…”
Section: Introductionmentioning
confidence: 99%
“…These are most frequent among boys, aged up to four years old, in the home environment, mainly in the kitchen. [26][27][28] Generally speaking, the victims of burns result in a significant number of episodes of inpatient treatment, with rates of 18.1%, while those from falls reach close to 8%, and those from road traffic accidents, a little over 16%. 27 Children of school age are also exposed to risks for accidents due to burns.…”
Section: "What Has Happened Here?" -Domestic Accidents Poisonings Amentioning
confidence: 99%
“…Data of the Unified Health System (SUS) showed that 80,607 people were hospitalized for injuries from this type of trauma in 2009, accounting about 9% of the total group of hospitalizations of external causes in SUS, according to Gawryszewski et al [5].…”
Section: Introductionmentioning
confidence: 99%
“…The Brazilian study of Gawryszewski et al [5], analyzing 761 cases of burns seen in emergency services in several national states, found that most of the victims were male (58.6%) and in the age group 30-49 years old (23.1%), followed by the age group of zero to nine years old (23.0%). The main agents were hot substances (43.6%) and fire/flame (24.2%).…”
Section: Introductionmentioning
confidence: 99%